IEEE GLOBECOM 2008 - 2008 IEEE Global Telecommunications Conference 2008
DOI: 10.1109/glocom.2008.ecp.826
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of a Partially Coherent System Using Constellation Rotation and Coordinate Interleaving

Abstract: The performance analysis of a system employing coordinate interleaving and constellation rotation, over Nakagamim fading channels, in the presence of phase noise as well as additive white Gaussian noise (AWGN) is presented. The phase locked loop (PLL) dynamics result in phase noise thereby introducing imperfect receiver phase estimates which are assumed to have Tikhonov densities. The resulting performance degradation of the system due to the phase noise is analyzed and an upper bound for the average probabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…It can be observed that a rotation operation requires 4 RMs and 2 RSs. However, when α = arctan (1/N ), the corresponding components are obtained by (18) and (19). As previously mentioned, the multiplication by a factor N can be implemented by (log 2 M ) /2 left-shifts.…”
Section: Complexity Analysismentioning
confidence: 93%
“…It can be observed that a rotation operation requires 4 RMs and 2 RSs. However, when α = arctan (1/N ), the corresponding components are obtained by (18) and (19). As previously mentioned, the multiplication by a factor N can be implemented by (log 2 M ) /2 left-shifts.…”
Section: Complexity Analysismentioning
confidence: 93%
“…Many papers tried to solve this problem, which can be classified mainly into two categories: rotation for uncoded systems [1], [2], [3], [4], [5] and for coded systems [6], [7], [8], [9], [10], [11], [12], [13], [14], [15]. As practical systems always require channel coding, optimization work for coded system is more important.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of the modulation diversity technique has been evaluated considering different scenarios, which include M-ary phase shift keying (M-PSK) and M-ary quadrature amplitude modulation (M-QAM) constellations for Rayleigh fading channels [5,7,8,12], Rician fading channels [13,14] and Nakagami-m fading channels [11,15]. However, in some specific scenarios, the tails of those fading distributions do not properly fit the experimental measured data, as discussed in [16].…”
Section: Introductionmentioning
confidence: 99%